Pelatihan Penggunaan Copywriting bagi Komunitas Kubependa Rawalumbu Bekasi - Nugroho, Fifto; Asruddin (Jurnal Pengabdian Masyarakat Gemilang (JPMG), 2022)
Rumah singgah disabilitas mandiri (KUBEPENDA) produce a variety of household processed products such as masks, processed snacks that have been packaged properly. Currently, this community has started online marketing through the marketplace. Therefore, promotion is needed so that this KUBEPENDA business can be widely known. By conducting training on the use of copywritng on products, online or offline stores. The method used is offline counseling in the form of providing customized materials and training on the use of the Canva application to design product packaging. After the presentation of the material, as well as conducting training and evaluation, it can be seen that this counseling is going well. From the results of the evaluation carried out by freeing participants to copy the products they produced themselves, it can be seen that the success of the training reached 66% of the total participants, the rest produced enough copies